Evaluation of Geometric and Atmospheric Doppler for GNSS-RO Payloads - L. Mohammadi; S. Amiri; G.R. Mohammadkhani (AUT Journal of Electrical Engineering, 2017)
To reduce the sampling rate in global navigation satellite system (GNSS)-radio occultation receivers, it is essential to establish a suitable estimation of Doppler frequency from the received signal in the satellite onboard receiver. This receiver is usually located on low earth orbit satellite and receives GNSS satellites signal in the occultation situation. The occurred Doppler on the signal contains the Geometric and Atmospheric segments. The Geometric Doppler’s value depends on the orbital situation of transmitter and receiver. However, Atmospheric Doppler depends on the signal propagation environment conditions. To investigate the nature of these two types of Doppler, we establish different missions on STK software environment for receivers located on different orbits from 450km altitude to 800km and 1500km with different orbital parameters and by considering the Global Positioning System satellites as the transmitters. We also study the value and nature of the Atmospheric Doppler by utilizing and analyzing the data produced by the COSMIC Data Analysis and Archive Databases Center. In signal tracking part of the receiver, the variation of Doppler is also important, in addition to the Doppler that is called phase acceleration. Therefore, the derivatives of Geometric Doppler related to the LEO satellites in different altitudes need to be considered.